Senegal : Poverty Reduction Strategy Paper; Second Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note discusses key findings of the Second Annual Progress Report (APR) on Senegal's Poverty Reduction Strategy Paper (PRSP). The APR acknowledges the uneven implementation of the PRSP in 2004 and highlights persistent weaknesses in key areas. It also recognizes that further progress is needed to foster a sustained rise in private investment and exports. The report points to progress in health and education, but at a pace that might not be sufficient to attain the Millennium Development Goals.